2004
DOI: 10.1017/s0143385704000069
|View full text |Cite
|
Sign up to set email alerts
|

Interval exchange transformations and foliations on infinite genus 2-manifolds

Abstract: For each of the following properties, there is an isometric generalized interval exchange transformation (i.e. isometric GIET) having such property: (a) non-trivial recurrence orbits are exceptional and the union of them is a dense set, moreover the intersection of the closure of two such orbits is the union of finite orbits; (b) coexistence of dense orbits and exceptional orbits; (c) existence of a dense sequence of exceptional orbitsMoreover, the isometric GIET can be suspended to a smooth foliation, without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
0
1
Order By: Relevance
“…'s in the literature, see for example Chacon transformations in [5] and the interesting way of modifying g.i.e.t. 's analysed by Gutierrez et al in [10], we have not found such examples when dealing with ∞-i.e.t. 's with flips.…”
Section: Infinite Interval Exchange Transformations and Proof Of Propcontrasting
confidence: 56%
“…'s in the literature, see for example Chacon transformations in [5] and the interesting way of modifying g.i.e.t. 's analysed by Gutierrez et al in [10], we have not found such examples when dealing with ∞-i.e.t. 's with flips.…”
Section: Infinite Interval Exchange Transformations and Proof Of Propcontrasting
confidence: 56%